2022
DOI: 10.1002/csr.2348
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to invest and the assurance of corporate social responsibility reports

Abstract: Recent research has found that the effect of corporate social responsibility (CSR) information on investment decisions will be eliminated when it is explicitly assessed, especially when CSR is not related to core business activities (immaterial CSR issues). We thus extend prior research by investigating whether (1) CSR assurance increases investors' willingness to invest when CSR performance is material or immaterial to core business activities and (2) CSR assurance moderates the effect of explicit assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…There is also a mixed response on independent directors and CSR assurance, with some showing no significance (Aladwey et al, 2022;Liao et al, 2018). Other studies also showed a positive, neutral and negative significance between independent directors and CSR assurance (Cuadrado-Ballesteros et al, 2017;Pratoomsuwan & Chiaravutthi, 2022). A possible reason for no significance and negative significance may include limited access to information on firm operations by independent directors (Cavaco et al, 2017).…”
Section: Board Characteristics and Csr Assurance Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a mixed response on independent directors and CSR assurance, with some showing no significance (Aladwey et al, 2022;Liao et al, 2018). Other studies also showed a positive, neutral and negative significance between independent directors and CSR assurance (Cuadrado-Ballesteros et al, 2017;Pratoomsuwan & Chiaravutthi, 2022). A possible reason for no significance and negative significance may include limited access to information on firm operations by independent directors (Cavaco et al, 2017).…”
Section: Board Characteristics and Csr Assurance Engagementmentioning
confidence: 99%
“…CSR assurance engagement creates credibility in the sustainability reports submitted to stakeholders (García‐Sánchez et al, 2022;Nicole & Swift, 2003; O'Dwyer & Owen, 2005). A consequence is that positive CSR with CSR assurance increases investors' confidence in their willingness to invest (Pratoomsuwan & Chiaravutthi, 2022). However, the engagement of CSR assurance removes the control of assurance from the firm to the outside organisation (Reeve, 2003), causing pressure on the firm (Maas et al, 2018; Park & Brorson, 2005; Perego & Kolk, 2012) to submit sustainability reports that have less whitewashed status (Laufer, 2003; Perks et al, 2013).…”
Section: Theory Literature Review and Hypotheses Developmentmentioning
confidence: 99%